Scleral Buckling for Rhegmatogenous Retinal Detachment Associated with Pars Planitis - Yong-Kyu Kim; Wontae Yoon; Jae Kyoun Ahn; Sung Pyo Park (Journal of Ophthalmology)
Purpose. To evaluate the surgical outcome of scleral buckling (SB) in rhegmatogenous retinal detachment (RRD) patients associated with pars planitis. Methods. Retrospective review of RRD patients (32 eyes of pars planitis RRD and 180 eyes of primary RRD) who underwent SB. We compared primary and final anatomical success rates and visual outcomes between two groups. Results. Primary and final anatomical success were achieved in 25 (78.1%) and 31 (96.8%) eyes in the pars planitis RRD group and in 167 eyes (92.7%) and 176 eyes (97.7%) in primary RRD group, respectively. Both groups showed significant visual improvement (p<0.001) and there were no significant differences in final visual acuity. Pars planitis RRD group was associated with higher rate of postoperative proliferative vitreoretinopathy (PVR) development (12.5% versus 2.8%, p=0.031). Pars planitis and high myopia were significant preoperative risk factors and pseudophakia was borderline risk for primary anatomical failure after adjusting for various clinical factors. Conclusions. Pars planitis associated RRD showed inferior primary anatomical outcome after SB due to postoperative PVR development. However, final anatomical and visual outcomes were favorable. RRD cases associated with pars planitis, high myopia, and pseudophakia might benefit from different surgical approaches, such as combined vitrectomy and SB.